2009
DOI: 10.1007/s00259-009-1218-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping brain morphological and functional conversion patterns in amnestic MCI: a voxel-based MRI and FDG-PET study

Abstract: The discordant topography between atrophy and hypometabolism reported in AD is already present at the aMCI stage. Posterior cingulate-precuneus hypometabolism seemed to be an early sign of memory deficit, whereas hypometabolism in the left temporal cortex marked the conversion to AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 51 publications
4
58
0
4
Order By: Relevance
“…İstatistiksel parametrik haritalama (SMP) yönteminin kullanıldığı 14 AH, 16 MCI hastasını içeren bir çalışmada; AH grubunda posterior singulat korteks, prekuneus, inferior parietal ve orta temporal loblarda hipometabolizma gözlenirken, MCI grubunda hipometabolizmanın posterior singulat girus ile sınırlı olduğu saptanmıştır (15). MCI'nın heterojen bir başlık olduğu bilinse de prospektif çalışmalar amnestik MCI'sı olup da sonradan AH gelişen hastaların erken evrede AH-benzeri bir glukoz hipometabolizması gösterdiğini belirtmişlerdir (16). FDG PET/BT primer demans tiplerinin ayırıcı tanısında da önemli bir role sahiptir.…”
Section: Alzheimer Hastalığında F-18 Fdg Pozitron Emisyontomografi/biunclassified
“…İstatistiksel parametrik haritalama (SMP) yönteminin kullanıldığı 14 AH, 16 MCI hastasını içeren bir çalışmada; AH grubunda posterior singulat korteks, prekuneus, inferior parietal ve orta temporal loblarda hipometabolizma gözlenirken, MCI grubunda hipometabolizmanın posterior singulat girus ile sınırlı olduğu saptanmıştır (15). MCI'nın heterojen bir başlık olduğu bilinse de prospektif çalışmalar amnestik MCI'sı olup da sonradan AH gelişen hastaların erken evrede AH-benzeri bir glukoz hipometabolizması gösterdiğini belirtmişlerdir (16). FDG PET/BT primer demans tiplerinin ayırıcı tanısında da önemli bir role sahiptir.…”
Section: Alzheimer Hastalığında F-18 Fdg Pozitron Emisyontomografi/biunclassified
“…A crucial issue is the finding of posterior cingulate hypometabolism aMCI patients who do not convert to AD after some years (from 1 to 2) of follow-up [20]. Nestor et al [21] have suggested that significant hypometabolism in the posterior cingulate is typical for all MCI patients, without a direct relationship to their future conversion.…”
Section: Fdg-pet Findings In Mild Cognitive Impairment (Mci) and Earlmentioning
confidence: 99%
“…In MCI patients, delayed episodic memory performance significantly correlated with hypometabolism in the frontal cortex (27). Comparison between the 2 MCI subtypes (amnestic and nonamnestic) showed temporal lobe hypometabolism in amnestic MCI subjects, possibly reflecting the conversion to AD (28,29). Glucose metabolism is a sensitive measure of change in cognition and functional ability both in AD and in MCI and has value in predicting future cognitive decline (30).…”
Section: Brain Glucose Metabolismmentioning
confidence: 99%